Theophylline-loaded pectin-based hydrogels. I. Effect of medium pH and preparation conditions on drug release profile - BATIREL, SAİME (WILEY, 2018)
In this study, a series of theophylline-loaded calcium pectin gel films were prepared in three different Ca+2 concentrations with three different methods for wound dressing applications. Drug release performance of the films were investigated in four different medium pH in order to mimic wound healing pH conditions. Hydrogel films were characterized by Fourier transform infrared spectroscopy, differential scanning calorimetry, scanning electron microscopy and atomic force microscopy. Their absorbency (fluid handling), swelling behavior, dehydration rate, dispersion characteristic, dressing pH determination, water vapor permeability, oxygen permeability, surface contact angle, flexibility, Shore A hardness, mean mass per unit area and thickness were determined. The effect of the hydrogels on wound healing was evaluated with an in vitro wound healing assay. After evaluating all data, we suggested that the hydrogel film prepared with swelling method using 7% or 10% crosslinker and dried at 26 degrees C is more suitable for controlled drug release process. We showed that between pH 3.25 and 7.12 the form of the hydrogel did not change, and drug release was continuous. (c) 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2018, 135, 46731.
Keywords: biomedical applications; biopolymers and renewable polymers; drug delivery systems; GEL-COATED PELLETS; DELIVERY; ENTRAPMENT; DRESSINGS; ALGINATE; CHITOSAN; BEADS; FILMS